PENGARUH KINERJA KEUANGAN DAN KARAKTERISTIK PERUSAHAAN TERHADAP PENGUNGKAPAN SUSTAINABILITY REPORT PADA PERUSAHAAN YANG LISTING DI BURSA EFEK INDONESIA TAHUN 2013-2015 - Rahman, Aulia Rayendra; Kamaliah, Kamaliah; Safitri, Devi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The purpose of this research is to analyze the effect of financial performance and corporate characteristics on disclosure sustainability report. The exammined variable of the reaserch are profitability, liquidity, firm size, and firm age as independent variables while disclosure sustainability report as dependent variable. The population in this study are all listed corporate in Indonesia Stock Exchange. The number of sample is 19 corporate by the number of observations were 57 (19x3). Observations that selected by using porposive sampling method. Data analysis using multiple linear regression at levels significance at 5% with the help of software SPSS version 23.0. The results of the study concluded that variable profitability, and firm age have significantly affect to disclosure sustainability report, while variable liquidity, and firm size not have an affect on disclosure sustainability reportKeyword : Disclosure, Sustainability Report, Profitability, Liquidity, Firm Size, Firm Age, Indonesia Stock Exchage.